2006
DOI: 10.3748/wjg.v12.i24.3924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extract from Ginkgo biloba on carbon tetrachloride-induced liver injury in rats

Abstract: EGb resists oxidative stress and thereby reduces chronic liver injury and liver fibrosis in rats with liver injury induced by CCl(4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…It was found that chronic administration of CCl 4 induced a significant increase (2.4‐fold) in the liver content of TBARS 9 weeks after starting CCl 4 intoxication compared with the control group. Similar observations have been reported previously 40,44,45 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was found that chronic administration of CCl 4 induced a significant increase (2.4‐fold) in the liver content of TBARS 9 weeks after starting CCl 4 intoxication compared with the control group. Similar observations have been reported previously 40,44,45 …”
Section: Discussionsupporting
confidence: 93%
“…Similar observations have been reported previously. 40,44,45 Oral treatment of animals with lisinopril, fosinopril or losartan significantly counteracted GSH depletion and lipid peroxidation induced by CCl 4 . However, fosinopril treatment did not show any significant improvement in liver GSH levels compared with the CCl 4 -intoxicated group.…”
Section: Discussionmentioning
confidence: 98%
“…CCl 4 is a potent hepatoxin producing centrilobular hepatic necrosis which is widely used for animal models of liver fibrosis. It has been reported that CYP450 in rat liver activates CCl 4 to a trichloromethyl free radical (CCl3• and/or CCl3OO•), and stimulates Kupffer cells to produce ROS, such as •O 2 − , H 2 O 2 and •OH, which damage the liver [9][11]. These ROS are eliminated by antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and CAT.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon tetrachloride (CCl 4 ) is an effective hepatotoxic agent under laboratory experimentations causes oxidative damages in experimental animal models. CCl 4 react with membrane lipids and converting into trichloromethyl radical (.CCl 3 ) and finally liver cells fibrosis during chronic cases [1, 2]. Multiple reports revealed that these free radicles also depleted the antioxidant enzymatic and non-enzymatic levels which are linked to hepatic injuries and fibrosis [3].…”
Section: Introductionmentioning
confidence: 99%